Purification of epithelial-type transforming growth factor by micro-preparative electrophoresis chromatography - Parnell, P G (BioTechniques, 1993)
The purification and recovery of biologically active epithelial-type transforming growth factor (TGFe) is described. In the final phase of purification, micropreparative electrophoretic chromatography was employed using a Tris-glycine-sodium dodecyl sulfate buffer system in an automated instrument. Briefly, partially purified protein preparations were separated in 2.5 x 50 mm, 10% polyacrylamide gel in electrophoresis tubes installed in the apparatus, electrophoresed under constant current of 1.5 mA for 400 min and recovered by automated fractionation and collection of the eluant from the tube gel. Aliquots of the eluted fractions were assayed in a biological system using SW-13 cell growth stimulation as an indicator of the presence of biologically active TGFe. Using the above procedure, TGFe was purified to within 95% homogeneity as assessed by silver-stained sodium dodecyl sulfate polyacrylamide gel electrophoresis